Pembentukan Harga Cabai Merah Keriting Secara Teoritis Dan Empiris - Dety Sukmawati; Euis Dasipah (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2021)
High demand for curly red chilies will cause prices to rise while production cannot fulfill consumer desires. This situation was caused by an imbalance of supply-demand, where the supply-demand imbalance can be caused by several changes such as changes in production technology, population growth or number of consumers, changes in income levels per capita and season (., Asriani, and Rasyid 2012). Research data as research subjects were 1) Price time series data, curly red chili production at production centers 2) Supply data of curly red chilies from Cikajang Garut Regency, Caringin Central Market, Gedebage Main Market and Kramat Jati Central Market, 3) Time series data price, production, supply, government policies and supporting data from the West Java Food Crops Agriculture Office, and related agencies. The data used were time series data and supporting data from: Price information centers in production centers, main markets and price information at the West Java Food Crops Agricultural Service, for each marketing agency data was carried out by tracing the marketing chain. The research analysis was carried out in several ways, namely theoretically and empirically at the production center and the wholesale market described descriptively. Theoretical price formation can be explained that prices was formed based on supply and demand. Prices derived from price formation can come from the District or Provincial Agriculture Office and be informed from the Commodity Price Information Center in production centers and forwarded to farmers, dealers, traders and wholesale markets. Price information can be conveyed to between market players, so that farmers and market players know your margin and profit. Empirically, it can be seen that price formation in production centers was not seen to be formed from supply and demand. The price in the wholesale market is the price determined by market players in the wholesale market based on the amount of supply entering the main market and price information between the parent markets. The information center at PIKJ does not have production data from production centers so that when the price hike occurs, the version of the Ministry of Agriculture is imports of chilies (